Adaptation from Conventional to Virtual Teaching Practices during COVID-19 Emergence: Perceptions of Multidisciplinary Teaching Faculty of Pakistan - Hani, Ume; Ansari, Asma Saher; Khan, Shujah Adil; Moten, Misbah Ashraf; Waseem, Farzeen S.; Sultan, Zohaib Khurshid (European Journal of General Dentistry, 2022)
Objectives The perceptions maintained by the teaching profession have a plausible influence on the effectiveness of online teaching practices, but they have not been well comprehended in many institutions in Pakistan. This study is the first to demonstrate how different academic disciplines address the challenges and opportunities regarding online teaching during coronavirus disease 2019 (COVID-19) and whether there exists a strong correlation between respondents' attitudes and their field of discipline.Materials and Methods A multi-centric cross-sectional survey was conducted online, and data gathered from the online survey were analyzed using SPSS version 16, demographic and categorical data were analyzed in frequencies and percentages. A relationship between the attitudes of teachers with their areas of discipline and a difference in response between genders and age groups were analyzed using a chi-square test.Results The findings of our study provide valuable understandings that most of the higher education faculty felt positively (64.1%) regarding the online mode of teaching. However, their perceived attitudes have a significant influence on the nature of their academic discipline.Conclusion These findings provide relevant suggestions to the core aspects of the use of the e-learning system during the COVID-19 pandemic to foster positive teaching experiences. The administrations and institutions can use it to identify the e-learning constraints within multiple fields of profession and help instructors generate quality materials that will reshape the framework of online education and preserve the practice of blended teaching even after the pandemic.
Keywords: online teaching; faculty; COVID-19